Ensino e aprendizagem da língua inglesa a distância - Aita, Fabiane Mernak (2017)
Tutor’s role in an online course is very important as a mediator in the pedagogical process. In order to this mediation occurs effectively, it is important it takes a problem-dialogic approach. So that, to problematize the situations in the online environment, it is necessary the tutor surfs fluently through all the Moodle activities and resources, then he will be able to enhance interaction, interactivity, autonomy and collaboration, concepts that go through the problem-dialogic practice. The following research, evolved in the Postgraduate Program in Network Educational Techonologies in the research line of Management in Educational Network Technologies, aimed to analize how the tutor’s work in the online learning environment of the e-Tec Idiomas sem Fronteiras from CTISM can intervene to improve the tutor-student interaction. Data has been obtained through the following instruments: survey, documental analysis, field journal and a semi-structure interview. The data analysis was done through Bardin content analysis and the categories listed were: Interaction and Communication; Training and Technological Fluency and Online English Language Teaching. As a result, it was noticeable the tutor and student’s lack of technological fluency about the Moodle environment as well as the lack of interaction among them. Another aspect was the difficulty the tutor and student had in detaching themselves from the traditional education that is, discrediting the possibility of interacting, developing a bond and learning through an online course. With the purpose of lessening the issues concerning interaction and interactivity, it was suggested to integrate the use of mobile applications into the practice of tutor and student who will be able to have access to the course from wherever they are and at any time and also to practice written and oral activities. As a product, we conclude this study with the proposition of some pedagogical guidelines that can help tutors on their daily tasks in the online educational practice.